Penyuluhan Motorik Anak di Taman Kanak-Kanak Al-Qur’an Kelurahan Mulyasari - Ida Wahidah; Selly Purnama; Endah Listyasari; Imam Badru Zaman (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2025)
The process of learning movement in TKA Al-Mukarromah and KOBER Al-Hasanah is a bit monotonous and tends to make students feel bored because games or learning movement such as gymnastics are only given the same. Such conditions are caused by the lack of knowledge of teachers in movement training materials, or games that contain motor elements. Based on this, it is very important for teachers in these schools to know how to teach good and correct movement to their students so that the movement given provides benefits. The objectives of this activity are: 1) Opening the insights of teachers in increasing scientific insight, 2) Providing counseling on motor movement material and how to convey movement material to students so that they do not get bored, and 3) Practicing together doing movement exercises for kindergarten children. The Community Scheme (PbM-KM) activity method is implemented in 4 stages, namely: 1) Coordinating with TKA Al-Mukarromah and KOBER Al-Hasanah, 2) Providing counseling on children's motor skills, 3) Practicing how to do good and correct motor exercises for kindergarten children, 4) Monitoring and evaluating the activities that have been carried out.